Profitability Intervention: Role of ESG Disclosure and Company Size on Financial Performance - Parwati, Tri Ayu; Rici, Suchi Avita; Fajar, Muhammad (GOVERNORS, 2025)
This study aims to determine the effect of esg disclosure, company size, on financial performance with profitability as an intervening variable. The population used in this study are IDXESGLeader companies listed on the Indonesia Stock Exchange (BEI) in 2019-2023. The sampling technique in this study was purposive sampling and obtained 17 IDXESGLeader companies with 85 observations. The analysis method used is multiple linear regression analysis. Based on the simultaneous test results that the esg disclosure variable, company size, and profitability affect financial performance. While with intervening variables, the simultaneous test results of ESG disclosure variables, company size, affect financial performance through profitability as an intervening variable. Based on the partial test results that ESG disclosure and company size have no significant effect on profitability, ESG disclosure has a significant effect on financial performance, company size affects company size, and profitability affects financial performance. Meanwhile, with the intervening variable, the partial test results of the ESG disclosure variable, company size have no effect on financial performance through profitability in IDXESGLeader companies listed on the Indonesia Stock Exchange (BEI) in 2019-2023.